Potential antecedents and consequences of negative effects for coaches. Issue 1 (2nd January 2019) - Graßmann, Carolin; Schermuly, Carsten C.; Wach, Dominika
ABSTRACT: Prior research showed that coaches often experience negative effects in their work. The present study explores their antecedents and impact on coaches' health and well-being. In a time-lagged design and an international sample, 275 coaches evaluated their last completed coaching process. Negative effects for coaches and their potential antecedents were assessed at t 1 and the consequences for coaches' health and well-being at t 2 . Results from structural equation modeling indicated that coaches experienced more negative effects when the relationship quality with their clients was low. When coaches perceived their client's goal attainment as low and a high number of negative effects for their clients, coaches felt less competent as a coach and experienced more negative effects for themselves. Coaches who experienced more negative effects at t 1 perceived more stress and impaired sleep eight weeks later ( t 2 ). This is the first study to present antecedents of negative effects for coaches and may assist coaches to prevent negative effects. The relationship to coaches' health and well-being eight weeks later support the importance of coaches' self-care. The use of a time-lagged design helps to rule out common method variance that may exist in prior research on the consequences of negative effects.